2019
DOI: 10.1016/j.meatsci.2018.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Suggestion for a subdivision of processed meat products on the Danish market based on their content of carcinogenic compounds

Abstract: Carcinogenic effects in humans are ascribed to processed meat by organisations such as International Agency for Research on Cancer, World Cancer Research Fund and American Institute for Cancer Research. However, the term 'processed meat' covers a heterogenic group of products whose content of potential hazards differ considerably. To improve estimates of associations between processed meat intake and cancer risk we investigated ways to divide processed meat into subgroups that more precisely reflects its carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…When estimating associations between meat intake and disease risk by comparing groups with high and low meat intake, respectively, it is pivotal to be aware which foods substitute meat in the low-meat diet. High meat intake is not necessarily confounded by an unhealthy diet, e.g., low in fruit, vegetables, whole-grain and dietary fiber intake and high in sugar and alcohol [ 97 ]. However, it was observed in analyses of dietary patterns in adult Danes that the 25% of the population with the highest reported meat intake along with an unhealthy diet (the highest quartile) have a red meat intake that is significantly higher (approximately 20% higher) than the 25% of the population with highest meat content in combination with a healthy diet (144 g/10 MJ compared with 121 g/10 MJ) [ 98 ].…”
Section: The Importance Of Confounders and Co-factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…When estimating associations between meat intake and disease risk by comparing groups with high and low meat intake, respectively, it is pivotal to be aware which foods substitute meat in the low-meat diet. High meat intake is not necessarily confounded by an unhealthy diet, e.g., low in fruit, vegetables, whole-grain and dietary fiber intake and high in sugar and alcohol [ 97 ]. However, it was observed in analyses of dietary patterns in adult Danes that the 25% of the population with the highest reported meat intake along with an unhealthy diet (the highest quartile) have a red meat intake that is significantly higher (approximately 20% higher) than the 25% of the population with highest meat content in combination with a healthy diet (144 g/10 MJ compared with 121 g/10 MJ) [ 98 ].…”
Section: The Importance Of Confounders and Co-factorsmentioning
confidence: 99%
“…High meat intake is not necessarily confounded by an unhealthy diet, e.g., low in fruit, vegetables, whole-grain and dietary fiber intake and high in sugar and alcohol [ 97 ]. However, it was observed in analyses of dietary patterns in adult Danes that the 25% of the population with the highest reported meat intake along with an unhealthy diet (the highest quartile) have a red meat intake that is significantly higher (approximately 20% higher) than the 25% of the population with highest meat content in combination with a healthy diet (144 g/10 MJ compared with 121 g/10 MJ) [ 98 ]. For processed meat, the difference is even higher (32%; 87 g/10 MJ for those with an unhealthy diet compared with 66 g/10 MJ along with the healthy diet).…”
Section: The Importance Of Confounders and Co-factorsmentioning
confidence: 99%
“…As concern in food safety investigations, the danger of food nitrite still gives rise to debate in the scientific community. Recently new analysis methods were developed and new parameters were proposed for the evaluation of risk exposure to nitrite [29][30][31]. Rather than the nitrite concentration, %ADI would be more informative, since ADI was established based meat products consumption and nitrite concentration.…”
Section: Figure 1 Nitrite Concentration In Categories Of Meat Productsmentioning
confidence: 99%
“…PAHs are a large group of persistent organic compounds containing two or more fused aromatic rings (Gong et al, 2018), which are considered potentially carcinogenic in humans because of their genotoxic properties (Mejborn et al, 2019). Although the mechanisms through which PAHs form in meats during grilling are not understood fully, some studies have reported three mechanisms of PAH formation in grilled meats, as follows: (i) the pyrolysis of organic compounds or fats in meat creates a layer on the meat containing PAHs;…”
Section: Introductionmentioning
confidence: 99%
“…However, undesirable substances, such as polycyclic aromatic hydrocarbons (PAHs) and heterocyclic aromatic amines, are produced during charcoal-grilling ( Wang et al, 2019 ). PAHs are a large group of persistent organic compounds containing two or more fused aromatic rings ( Gong et al, 2018 ), which are considered potentially carcinogenic in humans because of their genotoxic properties ( Mejborn et al, 2019 ). Although the mechanisms through which PAHs form in meats during grilling are not understood fully, some studies have reported three mechanisms of PAH formation in grilled meats, as follows: (i) the pyrolysis of organic compounds or fats in meat creates a layer on the meat containing PAHs; (ii) the incomplete combustion of coals produces smoke, which attaches to the surface of meat; and (iii) melting fats drip over the burning charcoal, causing the formation of PAHs that return to the meat via smoke ( García-Lomillo et al, 2017 ; Viegas et al, 2014 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%